Cultivating a calm attitude in the face of problems through Dhikr psychotherapy - Purwanti, Heni; Zumrotun Nafisah; Muhammad Novan Zulfahmi (Universitas Nahdlatul Ulama Surabaya, 2024)
Being calm through dhikr psychotherapy is very effective in dealing with problems. The aim of this research is to highlight the application of dhikr psychotherapy in helping someone achieve calm when facing challenges in dealing with various life problems. The research method used is library research. The results of research on dhikr psychotherapy have the impact of making people calm, confident and full of optimism. Remembrance psychotherapy exists as an alternative solution to relieve anxiety and lead individuals to mental peace. Through the repeated chanting of thayyibah sentences (positive speech) during dhikr activities, individuals are invited to experience inner peace and strengthen their belief in Allah SWT. The feelings, fear and anxiety that often haunt old age slowly fade away, replaced by deep calm and resignation. More than just calming the soul, remembrance psychotherapy also builds positive suggestions within the individual.